Implementasi Pendekatan Ekoteologi Pada Pembelajaran Pendidikan Agama Islam (PAI) Di UPT SDN 064027 - Rizki Rinaldi; Nasrun Salim Siregar (Jurnal Multidisiplin Indonesia, 2026)
The global environmental crisis is rooted in humanity’s exploitative behavior toward nature, necessitating education capable of instilling ecological awareness grounded in religious values. This study aims to describe the implementation of an ecotheological approach in Islamic Religious Education learning at UPT SDN 064027, the forms of ecotheological value integration within learning materials and processes, and its impact on students environmental awareness attitudes. The study employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation involving the school principal, IRE teachers, and students. The findings reveal that the implementation of ecotheology rests on the school’s vision and policies, which unite ritual piety with ecological piety, further reinforced through the exemplary conduct (uswah hasanah) of IRE teachers. Ecotheological value integration is carried out through the reinterpretation of IRE materials based on the concepts of Khalifah (stewardship) and Amanah (trust), the transformation of learning processes through outdoor learning in the school garden to understand Ayat Kauniyah (verses of the natural world), the utilization of containers to collect leftover ablution water for plant conservation and the use of environment-based learning media. This approach has proven to have a significant impact on students’ environmental awareness, reflected across cognitive, affective, and psychomotor domains, and has successfully mitigated the value-action gap between religious value comprehension and real-world action. Thus, the integration of ecotheology in IRE learning plays a strategic role in shaping students of strong faith who are committed to ecosystem sustainability.